Cement composition and method for producing the cement composition

The cement composition addresses DEF-related expansion and strength issues by optimizing the ratios of cement clinker, gypsum, and coal ash, achieving high compressive strength and reduced emissions.

JP7604109B2Active Publication Date: 2024-12-23MITSUBISHI UBE CEMENT CORP
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2020064404
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-03-31
Publication Date
2024-12-23
Estimated Expiration
2040-03-31

AI Technical Summary

Technical Problem

Existing cement compositions face issues with delayed ettringite formation (DEF) leading to expansion and deterioration, especially when high amounts of gypsum are used for early strength development, which reduces the amount of waste materials and increases carbon emissions.

Method used

A cement composition with a specific formulation that includes a range of cement clinker, gypsum, and mixed materials, adjusted to satisfy a mathematical relationship that balances the amounts of tricalcium aluminate, gypsum, and coal ash to suppress DEF while maintaining high compressive strength and reducing emissions.

Benefits of technology

The composition effectively suppresses DEF expansion and enhances compressive strength during demolding after high-temperature curing, while reducing carbon emissions by incorporating a higher proportion of waste materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007604109000001
    Figure 0007604109000001
  • Figure 0007604109000002
    Figure 0007604109000002
  • Figure 0007604109000003
    Figure 0007604109000003
Patent Text Reader

Abstract

To provide a cement composition capable of being produced with more reduction of the amount of CO2 emission during cement production than before even when there are large amounts of SO3 and C3A, capable of suppressing expansion with DEF, and capable of producing a cement hardened body excellent in compressive strength during form removal after high temperature curing.SOLUTION: Provided is a cement composition containing cement clinker in which the amount of C3S calculated by Bogue's formula is 20.0-80.0 mass% and the amount of C3A is 6.0-15.0 mass%, gypsum, and an admixture. In the cement composition, the content of the gypsum, assuming that the total amount of the cement clinker, the gypsum and the admixture is 100 mass%, is 1.8-3.5 mass% expressed in terms of SO3, and the content of the admixture, assuming that the total amount of the cement clinker, the gypsum and the admixture is 100 mass%, is 2.0-30.0 mass%. The amount of C3S, the amount of C3A, the content of coal ash based on 100 mass% of the total content of the cement clinker, the gypsum and the admixture, and the amount of SO3 derived from the gypsum, satisfy the relation of [amount of C3S (mass%)]≤α×[amount of C3A (mass%)-9.0]+2.0×[content of coal ash (mass%)]+β-10.0×[amount of SO3]...formula (1). [In the formula (1), α is represented by α=(-2.5×[amount of SO3 (mass%)])×(100-[ratio of hemihydrate gypsum (mass%)]) / 100...formula (2). The ratio of hemihydrate gypsum denotes a ratio of the hemihydrate gypsum to the whole amount of the gypsum, the ratio of the hemihydrate gypsum is 0-90 mass%, and β is a real number of 75.0 or less.]SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to cement compositions and methods for making cement compositions. [Background technology]

[0002] In high-early-strength Portland cement and white Portland cement, the amount of gypsum added may be higher than that in ordinary Portland cement in order to achieve early strength development and ease setting. However, an increase in the amount of SO3 in the cement makes delayed ettringite formation (DEF) more likely to occur, increasing the risk of deterioration phenomena such as cracks occurring in the hardened cement body. In fact, it has been reported that high-early-strength Portland cement and white Portland cement are prone to expansion of the hardened cement body due to DEF (Non-Patent Document 1).

[0003] DEF refers to the regeneration phenomenon of ettringite as follows. First, the temperature inside the concrete rises significantly due to the initial high-temperature curing and heat generation of the cement composition, causing the decomposition of ettringite (a compound represented by 3CaO·Al2O3·3CaSO4·32H2O), which should have been generated in the initial stage. Then, when moisture is supplied during the service of the concrete, the phenomenon of ettringite regeneration occurs. Ettringite is also known to expand with crystallization, and DEF causes expansion in the hardened body structure, causing serious deterioration such as cracks in the concrete. For example, Non-Patent Document 2 reports cases of expansion of secondary concrete products (precast concrete products) in Japan. It has been reported that white cement with a high content of SO3 and C3A is deteriorated by expansion associated with DEF due to high temperature history caused by steam curing.

[0004] Various measures to suppress DEF have been studied. Non-Patent Document 3 shows that expansion due to DEF is less likely to occur when low-heat Portland cement or moderate-heat Portland cement is used than when normal Portland cement or high-early-strength Portland cement is used. However, in these cements that suppress expansion due to DEF, the C3A content is set low for the purpose of suppressing heat generation, etc., which causes a problem of reducing the amount of waste material used per unit amount of cement that can be added to the raw materials.

[0005] It is known that cement clinker, which is a raw material for cement, emits a large amount of CO2 during its manufacturing process. From the viewpoint of preventing global warming, it is desired to further increase the content of admixtures such as coal ash in the cement composition in order to reduce the cement content. As an admixture, for example, limestone is also known in addition to coal ash. From the viewpoint of limiting CO2 emissions, the incorporation of limestone is effective, but it has been reported that the addition of limestone promotes DEF (for example, Non-Patent Document 3).

[0006] In the production of secondary products, strength at the time of demolding after high-temperature curing is required to increase formwork turnover and improve yield. Patent Document 1 discloses a cement composition that sufficiently improves compressive strength at the time of demolding by adding chlorine bypass dust to the cement composition, and mortar and concrete prepared using the cement composition. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2007-176774 A [Non-patent literature]

[0008] [Non-Patent Document 1] "Guidelines for Crack Control in Mass Concrete 2016", 2016, Japan Concrete Institute [Non-Patent Document 2] Yuichiro Kawabata, Hiromichi Matsushita, "Study on DEF expansion in concrete cured with high temperature steam", Journal of the Japan Society of Civil Engineers, Vol. E2 (Materials and Concrete Structures), 2011, Vol. 67, No. 4, pp. 549-563 [Non-Patent Document 3] Shingo Asamoto et al., "Study on the effect of carbonate ions on delayed ettringite formation", Proceedings of the Japan Concrete Institute, 2016, Vol. 28, No. 1, pp. 819-824 Summary of the Invention [Problem to be solved by the invention]

[0009] The above measures have the problem that low-heat Portland cement and moderate-heat Portland cement have a low amount of C3A per unit of cement, resulting in less waste material used as raw materials. However, if the C3A content is high, there is a risk of DEF generation and reduced strength at removal from formwork. Also, as mentioned above, if the SO3 content is high, there is a high risk of deterioration of the hardened cement body due to DEF generation.

[0010] The present disclosure aims to provide a cement composition that can be used to produce a hardened cement body that can reduce CO2 emissions during cement production compared to conventional methods, suppresses expansion associated with DEF even when the amounts of SO3 and C3A are high, and has excellent compressive strength when demolded after high-temperature curing, and a method for producing the same. [Means for solving the problem]

[0011] The present disclosure relates to a cement clinker having a C3S content of 20.0 to 80.0 mass% and a C3A content of 6.0 to 15.0 mass% calculated by the Bogue formula, gypsum, and an admixture, the content of the gypsum being 1.8 to 3.5 mass% in terms of SO3, with the total amount of the cement clinker, the gypsum, and the admixture being 100 mass%, and the content of the admixture being 1.8 to 3.5 mass% in terms of SO3, and The total amount of the admixture is 100 mass%, and the coal ash content and the SO3 content derived from the gypsum relative to 100 mass% of the total content of the C3S amount, the C3A amount, the cement clinker, the gypsum, and the admixture are expressed as follows: [C3S amount (mass%)] ≦ α × [C3A amount (mass%) - 9.0] + 2.0 × [coal ash content (mass%)] + β - 10.0 × [SO3 amount (mass%)] ... formula (1) [In the above formula (1), the α is expressed as α = (-2.5 × [SO3 amount (mass%)]) × (100 - [gypsum hemihydrate ratio (mass%)]) / 100 ... formula (2), and the gypsum hemihydrate ratio indicates the ratio of gypsum hemihydrate to the total amount of gypsum, the gypsum hemihydrate ratio is 0 to 90 mass%, and the β is a real number of 75.0 or less. The present invention provides a cement composition which satisfies the relationship:

[0012] The above cement composition contains cement clinker with a relatively high C3A content and gypsum, and the gypsum content is also relatively high, but the C3S content, the C3A content, the coal ash content relative to 100 mass% of the total content of the cement clinker, the gypsum, and the admixture, and the SO3 content derived from the gypsum satisfy the relationship of the above formula (1), thereby suppressing expansion due to DEF and making it possible to produce a hardened cement body that has excellent compressive strength when demolded after high-temperature curing. The reason why the above-mentioned effect is obtained is unclear, but the inventors speculate that it is because the higher the C3S content, C3A content, and SO3 content, the more likely DEF is to occur, and the higher the coal ash content and the gypsum hemihydrate content, the more DEF is suppressed, so that it is necessary to adjust the C3S content according to the C3A content, coal ash content, SO3 content, and gypsum hemihydrate ratio.

[0013] The cement clinker may contain SO3 and R2O, and the amount of SO3 may be 0.10 to 2.00 mass% and the amount of R2O may be 0.10 to 2.00 mass% in 100 mass% of the cement clinker. By having the above composition of the cement clinker, it is possible to obtain an appropriate pot life while suppressing DEF.

[0014] The above cement composition has a Blaine specific surface area of ​​3000 to 6000 cm 2 When the Blaine specific surface area of ​​the cement composition is within the above range, the cement composition can achieve both sufficient strength development and appropriate heat of hydration.

[0015] The admixture may contain limestone, and the content of the limestone may be 2.0 to 22.5 mass% based on the total amount of the admixture. By including a predetermined amount of limestone as an admixture, it is possible to reduce CO2 emissions, reduce the heat of hydration of the cement composition, and improve the demolding strength.

[0016] The admixture may contain coal ash, and the content of the coal ash may be 15.0 to 85.0 mass% based on the total amount of the admixture. When the content of the coal ash is within the above range, the hydration heat of the cement composition can be reduced and the demolding strength can be improved.

[0017] The Blaine specific surface area of ​​the above coal ash is 3900 to 10000 cm 2 When the Blaine specific surface area of ​​the coal ash is within the above range, the DEF expansion can be suppressed and the strength can be increased.

[0018] The coal ash may have a 4 μm residue of 40 to 85% by volume and a 32 μm residue of 0 to 20.0% by volume. When the coal ash has the particle size distribution as described above, it is possible to increase strength, suppress DEF, and reduce adiabatic temperature rise.

[0019] The cement composition may further contain a hardening accelerator, and the content of the hardening accelerator may be 0.1 to 20.0 parts by mass relative to 100 parts by mass of the total amount of the cement clinker, the gypsum, and the admixture. By containing a predetermined amount of the hardening accelerator, it is possible to obtain appropriate workability while increasing the early strength.

[0020] One aspect of the present disclosure includes a step of mixing cement clinker having a C3S amount of 20.0 to 80.0 mass% and a C3A amount of 6.0 to 15.0 mass% calculated by the Bogue formula, with gypsum and an admixture, wherein in the step, the content of the gypsum is 1.8 to 3.5 mass% in terms of SO3, with the total amount of the cement clinker, the gypsum and the admixture being 100 mass%, and the content of the admixture is 1.8 to 3.5 mass% in terms of SO3, with the total amount of the cement clinker, the gypsum and the admixture being 100 mass%, -, the total amount of the gypsum and the admixture is 100 mass%, and the C3S amount, the C3A amount, the coal ash content relative to the total content of the cement clinker, the gypsum, and the admixture being 100 mass%, and the SO3 amount derived from the gypsum are [C3S amount (mass%)] ≦ α × [C3A amount (mass%) - 9.0] + 2.0 × [coal ash content (mass%)] + β - 10.0 × [SO3 amount (mass%)] ...Equation (1), [In the above equation (1), α is expressed by α=(-2.5×[amount of SO3 (mass %)])×(100-[proportion of gypsum hemihydrate (mass %)]) / 100 ...Equation (2), in which the proportion of gypsum hemihydrate indicates a proportion of gypsum hemihydrate to the total amount of gypsum, the proportion of gypsum hemihydrate is 0 to 90 mass%, and β is a real number of 75.0 or less.], characterized in that the blending ratio of the cement clinker, the gypsum, and the admixture is adjusted so as to satisfy the relationship of

[0021] The method for producing the cement composition includes a step of mixing cement clinker, gypsum, and an admixture so that the cement clinker contains gypsum and has a relatively high C3A content, and the gypsum content is also relatively high. By adjusting the mix so that the C3S amount, the C3A amount, the coal ash content relative to 100 mass% of the total content of the cement clinker, the gypsum, and the admixture, and the SO3 amount derived from the gypsum satisfy the relationship of the following formula (1), the obtained cement composition suppresses expansion associated with DEF, and it is possible to produce a hardened cement body that has excellent compressive strength when demolded after high-temperature curing. Effect of the Invention

[0022] According to the present disclosure, it is possible to provide a cement composition that can produce a hardened cement body that has excellent compressive strength when demolded after high-temperature curing, by suppressing expansion associated with DEF even when the amounts of SO3 and C3A are high, and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] Hereinafter, embodiments of the present disclosure will be described. However, the following embodiments are merely examples for explaining the present disclosure, and are not intended to limit the present disclosure to the following contents. In the following description, when it is written "X to Y" (X and Y are arbitrary numbers), it means "X or more and Y or less" unless otherwise specified.

[0024] One embodiment of the cement composition contains cement clinker having a C3S content of 20.0 to 80.0 mass% and a C3A content of 6.0 to 15.0 mass% calculated by the Bogue formula, gypsum, and an admixture. The content of the gypsum is 1.8 to 3.5 mass% in terms of SO3, with the total amount of the cement clinker, the gypsum, and the admixture being 100 mass%. The content of the admixture is 2.0 to 30.0 mass%, with the total amount of the cement clinker, the gypsum, and the admixture being 100 mass%.

[0025] In the cement composition, the C3S amount, the C3A amount, the coal ash content relative to 100% by mass of the total content of the cement clinker, the gypsum, and the admixture, and the SO3 amount derived from the gypsum relative to 100% by mass of the total content of the cement clinker, the gypsum, and the admixture satisfy the relationship of the following formula (1). The coal ash content is 0 to 22.5% by mass based on the total content of the cement clinker, the gypsum, and the admixture.

[0026] [C3S amount (mass%)]≦α×[C3A amount (mass%)-9.0]+2.0×[coal ash content (mass%)]+β-10.0×[SO3 amount (mass%)] …Formula (1)

[0027] In the above formula (1), the above α is a value represented by the following formula (2): In the above formula (1), the above β is an integer of 75.0 or less, preferably 75.0, more preferably 70.0, and even more preferably 65.0.

[0028] α=(-2.5×[SO3 amount (mass%)])×(100-[gypsum hemihydrate ratio (mass%)]) / 100…Formula (2)

[0029] The proportion of gypsum hemihydrate in the above formula (2) indicates the proportion (mass%) of gypsum hemihydrate to the total amount of gypsum in the cement composition, and means the value calculated by the following formula (3). The "total mass" in the following formula (3) means the sum of the masses of all gypsum in the cement composition, including gypsum added internally to a base cement obtained by pulverizing cement clinker and gypsum, and gypsum added externally to the base cement. In the above cement composition, the proportion of gypsum hemihydrate is 0 to 90 mass%.

[0030] [Gypsum hemihydrate ratio (mass%)] = 100 × [total mass of gypsum hemihydrate (mass%)] / [total mass of gypsum (mass%)] ... Formula (3)

[0031] The Bogue formula is a formula widely used to calculate the content of major minerals in cement based on its chemical composition. By using the Bogue formula shown below, the contents of tricalcium silicate (3CaO·SiO2, denoted as C3S), dicalcium silicate (2CaO·SiO2, denoted as C2S), and tricalcium aluminate (3CaO·Al2O3, denoted as C3A) in cement clinker can be calculated. Note that "%" in the following formula means "mass %".

[0032] <Bogue formula> C3S [%] = (4.07×CaO [%]) - (7.60×SiO2 [%]) - (6.72×Al2O3 [%]) - (1.43×Fe2O3 [%]) - (2.85×SO3 [%]) C2S [%] = (2.87×SiO2 [%]) - (0.754×C3S [%]) C3A [%] = (2.65×Al2O3 [%]) - (1.69×Fe2O3 [%]) C4AF [%] = 3.04×Fe2O3 [%]

[0033] By designing the cement clinker so that the amount of interstitial phases such as C3A and C4AF increases, the amount of waste by-products containing a large amount of Al and Fe, such as fly ash and slag, used as cement clinker raw materials can be increased, and a cement composition desirable from the perspective of reducing the environmental load can be provided.

[0034] The lower limit of the C3S content in the cement clinker is 20.0% by mass or more, preferably 30.0% by mass or more, more preferably 33.0% by mass or more, even more preferably 37.0% by mass or more, even more preferably 41.0% by mass or more, and particularly preferably 45.0% by mass or more. By the lower limit of the C3S content being within the above range, the initial strength of the cement composition during hardening can be further improved. The upper limit of the C3S content in the cement clinker is 80.0% by mass or less, preferably 65.0% by mass or less, more preferably 60.0% by mass or less, even more preferably 54.0% by mass or less, and particularly preferably 48.0% by mass or less. By the upper limit of the C3S content being within the above range, the heat generation during hardening of the cement composition can be further suppressed, the decomposition of ettringite can be suppressed, and the generation of DEF can be further suppressed. In addition, if the C3S content exceeds 80.0% by mass, it becomes difficult to prepare the cement clinker.

[0035] The lower limit of the C3A content in the cement clinker is 6.0% by mass or more, preferably 8.0% by mass or more, more preferably 9.0% by mass or more, even more preferably 9.5% by mass or more, even more preferably more than 10.0% by mass, and particularly preferably 10.3% by mass or more. By setting the lower limit of the C3A content within the above range, a cement composition can be produced in which the amount of waste and by-products such as coal ash used as the cement clinker raw material is increased. The upper limit of the C3A content in the cement clinker is 15.0% by mass or less, preferably 14.0% by mass or less, more preferably 13.5% by mass or less, even more preferably 12.5% ​​by mass or less, and particularly preferably less than 10.5% by mass. By setting the upper limit of the C3A content within the above range, the increase in adiabatic temperature rise during hardening of the cement composition can be further reduced, and the expansion due to DEF can be further suppressed.

[0036] The C3A content and C3S content in this specification refer to values ​​calculated by the Bogue formula using chemical analysis values ​​of cement clinker measured in accordance with the method described in JIS R 5204 "Fluorescent X-ray analysis method for cement."

[0037] Cement clinker may contain SO3 and R2O.

[0038] The amount of SO3 in the cement clinker is preferably 0.10 to 2.00 mass%, more preferably 0.15 to 1.50 mass%, further more preferably 0.20 to 1.20 mass%, and particularly preferably 0.25 to 0.75 mass%, based on 100 mass% of the cement clinker. By keeping the amount of SO3 within the above range, it is possible to further increase the amount of waste material used during burning of the cement clinker, and it is possible to further suppress DEF in the hardened cement body obtained from the cement composition containing the cement clinker.

[0039] The amount of SO3 in the cement clinker means a chemical analysis value of the cement clinker measured in accordance with the method described in JIS R 5204 "Fluorescent X-ray analysis method for cement."

[0040] The amount of RO in the cement clinker is preferably 0.10 to 2.00 mass%, more preferably 0.15 to 1.50 mass%, further more preferably 0.20 to 1.20 mass%, and particularly preferably 0.25 to 0.75 mass%, based on 100 mass% of the cement clinker. By keeping the amount of RO within the above range, it is possible to further increase the amount of waste material used during burning of the cement clinker, and it is possible to further suppress DEF in the hardened cement body obtained from the cement composition containing the cement clinker.

[0041] The amount of RO in cement clinker is a value calculated from the following formula using the chemical analysis value of the cement clinker measured in accordance with the method described in JIS R 5204 "Method for fluorescent X-ray analysis of cement." The amount of RO is used in quality standards as the total amount of alkali in cement. In the formula below, "%" means "% by mass." R2O[%]=Na2O[%]+0.658×K2O[%]

[0042] For example, gypsum dihydrate, hemihydrate, and anhydrous gypsum can be used. One type of gypsum may be used alone, or a combination of two or more types may be used. The cement composition has a relatively high content of gypsum. The content of gypsum in the cement composition is 1.8 to 3.5 mass%, preferably 1.9 to 3.0 mass%, and more preferably 2.0 to 2.6 mass%, calculated as SO3, with the total content of the cement clinker and the gypsum taken as 100 mass%. By having the content of gypsum within the above range, the compressive strength at the time of demolding during high-temperature curing of the cement composition and the strength development at room temperature can be improved. In addition, by having the content of gypsum within the above range, the occurrence of DEF can be suppressed while the pot life can be sufficiently secured.

[0043] The content of gypsum hemihydrate is adjusted so as to satisfy the gypsum hemihydrate ratio in the above formula (2). The gypsum hemihydrate ratio is 0 to 90 mass%, preferably 10 to 80 mass%, more preferably 20 to 60 mass%, and even more preferably 30 to 50 mass%. By having the gypsum hemihydrate ratio within the above range, it is possible to increase the demolding strength at high temperatures and further improve the DEF suppression effect. Furthermore, by setting the gypsum hemihydrate ratio to 90 mass% or less, it is possible to maintain appropriate coagulation and fluidity.

[0044] The cement composition may contain the above-mentioned cement clinker and gypsum as a base cement (a mixed and ground product of cement clinker and gypsum) which has been mixed and ground in advance.

[0045] The Blaine specific surface area of ​​the base cement is preferably 3000 to 5000 cm 2 / g, and more preferably 3100 to 4500 cm 2 / g, and more preferably 3150 to 4000 cm 2 When the Blaine specific surface area is within the above range, the compressive strength of the hardened cement body when demolded can be improved, the initial heat of hydration of the cement composition can be reduced, and the DEF in the hardened cement body can be further suppressed.

[0046] In this specification, the term "Blaine specific surface area" refers to a value measured in accordance with the method described in JIS R 5201:2015 "Physical test methods for cement."

[0047] The admixture preferably contains an appropriate amount of limestone. The inclusion of limestone can reduce CO2 emissions in the production of the cement composition and can further improve the compressive strength of the hardened cement body obtained by high-temperature curing. The admixture may further contain coal ash, which can further suppress the expansion of the hardened cement body associated with DEF and further improve the compressive strength of the hardened cement body obtained by high-temperature curing.

[0048] The content of the admixture is preferably high from the viewpoint of low carbonization including reduction in CO2 generation in the production of the cement composition, while being low from the viewpoint of improving the physical properties (e.g., compressive strength, etc.) of the hardened cement body. The content of the admixture is 2.0 to 30.0 mass%, preferably 2.5 to 27.5 mass%, more preferably 3.0 to 20.0 mass%, even more preferably 4.0 to 15.0 mass%, and particularly preferably more than 5.0 mass% and 12.5 mass% or less, based on 100 mass% of the total content of the cement clinker, the gypsum, and the admixture.

[0049] As the limestone, for example, powders mainly composed of calcium carbonate, such as limestone powder that is generally available on the market, and kansui stone powder, can be used. The limestone preferably includes those conforming to the minor mixing components described in JIS R 5210 "Portland cement".

[0050] The Blaine specific surface area of ​​limestone is preferably 2500 to 10000 cm 2 / g, and more preferably 4000 to 9000 cm 2 / g, and more preferably 6000 to 8000 cm 2 / g. The Blaine specific surface area of ​​limestone is 2500 cm 2 / g or more, the reactivity of the cement composition can be improved. 2 / g or less, deterioration of handleability can be suppressed.

[0051] The content of limestone is preferably low from the viewpoint of suppressing DEF, while being high from the viewpoint of low carbonization including reducing the amount of CO2 generated in the production of the cement composition. The content of limestone is preferably 2.0 to 22.5 mass%, more preferably 2.2 to 17.0 mass%, more preferably 2.5 to 12.5 mass%, and even more preferably more than 2.5 mass% and 10.0 mass% or less, based on the total content of the cement clinker, the gypsum, and the admixture as 100 mass%. By having the content of limestone within the above range, the heat of hydration can be further reduced, and the strength of the hardened cement body can be further improved. By having the content of limestone within the above range, the initial and long-term strength development of the hardened cement body can be further improved. The addition of an appropriate amount of limestone contributes to strength enhancement and reduction of heat of hydration, but if the amount added exceeds 22.5 mass%, the initial and long-term strength development decreases and has an adverse effect on DEF expansion.

[0052] The coal ash may be, for example, coal ash discharged from a coal-fired power plant. The above-mentioned mixture may contain other components in addition to coal ash and limestone. For example, ash obtained when coal, which is the main fuel, and biomass fuel derived from wood chips, coconut shells, sewage sludge, etc. are charged and mixed as a power generation boiler fuel in a coal-fired power plant can also be used as the mixture.

[0053] The Blaine specific surface area of ​​the coal ash is preferably 3900 to 10000 cm 2 / g, and more preferably 4200 to 8000 cm 2 / g, and more preferably 4500 to 6500 cm 2 / g, and even more preferably 5000 to 6000 cm 2 / g. The Blaine specific surface area of ​​coal ash can be adjusted, for example, by classification, crushing, etc. of coal ash. The Blaine specific surface area of ​​coal ash may also be adjusted by mixing coal ashes having different Blaine specific surface areas, or by mixing crushed coal ash with classified coal ash. Examples of the classification method of coal ash include air classification, electrostatic classification, sieve classification, gravity field classification, and centrifugal field classification. Examples of the pulverization method of coal ash include a method using equipment such as a ball mill, a jet mill, a rod mill, and a blade mill.

[0054] The particle size of the coal ash can be adjusted appropriately. The coal ash preferably has a 4 μm residue of 40 to 85 vol. % and a 32 μm residue of 0 to 20.0 vol. % or less, more preferably has a 4 μm residue of 40 to 80 vol. % and a 32 μm residue of 0 to 10.0 vol. % or less, and even more preferably has a 4 μm residue of 65 to 77.5 vol. % and a 32 μm residue of 0 to 5.0 vol. % or less. By having the 4 μm residue of the coal ash be 40 vol. % or more, the content of fine coal ash particles can be reduced and the deterioration of the handleability can be suppressed. By having the 4 μm residue of the coal ash be 40 vol. % or more, the increase in the adiabatic temperature rise during hardening of the cement composition can be further suppressed, and the DEF suppression effect can be maintained for a longer period of time. By keeping the 32 μm residue of the coal ash at 20.0 volume % or less, the content of coarse particles in the coal ash is low, which suppresses a decrease in pozzolanic reactivity and further suppresses a decrease in the strength of the hardened cement body (e.g., compressive strength, etc.) and a decrease in the DEF inhibitory effect.

[0055] The coal ash content is preferably 15.0 to 85.0 mass% based on the total amount of the admixture, more preferably 25.0 to 75.0 mass%, further preferably 35.0 to 60.0 mass%, and particularly preferably 45.0 to 55.0 mass%. By setting the coal ash content in the admixture within the above range, the DEF expansion in the hardened cement body can be further suppressed, and the compressive strength of the hardened cement body obtained by high-temperature curing of the cement composition can be further improved.

[0056] A larger coal ash content is desirable from the viewpoint of suppressing DEF, while a smaller coal ash content is desirable from the viewpoint of improving the physical properties (e.g., compressive strength) of the hardened cement body. The coal ash content is preferably 0 to 22.5 mass%, more preferably 1.0 to 17.0 mass%, even more preferably 1.5 to 12.5 mass%, and particularly preferably 2.5 to 7.5 mass%, based on 100 mass% of the total content of the cement clinker, the gypsum, and the admixture.

[0057] A mortar composition or a concrete-forming composition can be produced by adding, for example, fine aggregate, coarse aggregate, water and / or admixtures, and hardening accelerators to the above-mentioned cement composition. Mortar and concrete formed using the above-mentioned cement composition can exhibit excellent adiabatic temperature rise suppression, strength enhancement, and DEF suppression effects.

[0058] The fine aggregate may be one specified in JIS A 5005 "Crushed Stone and Crushed Sand for Concrete". Examples of fine aggregate include river sand, land sand, sea sand, crushed sand, silica sand, hard blast furnace slag fine aggregate, blast furnace slag fine aggregate, copper slag fine aggregate, and electric furnace oxidized slag fine aggregate. The fine aggregate may be used alone or in combination. The content of the fine aggregate in the above-mentioned cement composition may be, for example, 50 to 500 parts by mass with respect to 100 parts by mass of the total amount of the cement clinker, the gypsum, and the admixture.

[0059] The coarse aggregate may be one specified in JIS A 5005 "Crushed Stone and Crushed Sand for Concrete". Examples of the coarse aggregate include gravel, crushed stone, blast furnace slag coarse aggregate, and electric furnace oxidized slag coarse aggregate. One type of coarse aggregate may be used alone, or a combination of two or more types may be used. The content of the coarse aggregate in the above-mentioned cement composition is preferably 50 to 500 parts by mass relative to 100 parts by mass of the total amount of the cement clinker, the gypsum, and the admixture.

[0060] Examples of water include tap water, distilled water, and deionized water. The content of water in the above-mentioned cement composition is preferably 20 parts by mass or more and 60 parts by mass or less with respect to 100 parts by mass of the total amount of the above-mentioned cement clinker, the above-mentioned gypsum, and the above-mentioned admixture. By setting the content of water in the cement composition within the above-mentioned range, it is possible to sufficiently ensure the predetermined fresh properties (fluidity, air content, etc.) and moldability, and also to sufficiently suppress the decrease in the compressive strength and durability of the obtained cement hardened body.

[0061] Examples of the admixture include AE ​​agents, water reducing agents, AE water reducing agents, high performance water reducing agents, high performance AE water reducing agents, superplasticizers, antifoaming agents, shrinkage reducing agents, setting accelerators, setting retarders, and thickeners. Depending on the required performance, the admixture may be used alone or in combination. The content of the admixture in the above-mentioned cement composition is preferably 0.01 to 2 parts by mass with respect to 100 parts by mass of the total amount of the cement clinker, the gypsum, and the admixture.

[0062] Examples of the hardening accelerator include potassium sulfate, sodium sulfate, lithium sulfate, anhydrous gypsum, quicklime, slaked lime, calcium nitrite, calcium nitrate, calcium chloride, alkali aluminate, alkali carbonate, triethanolamine, triisopropanolamine, methyldiethanolamine, diethanolisopropanolamine, calcium formate, maleic anhydride, calcium rhodanate, CSH nanoparticles, and calcium thiocyanate. One hardening accelerator may be used alone, or a combination of two or more may be used.

[0063] The content of the hardening accelerator in the above-mentioned cement composition is preferably 0.1 to 20.0 parts by mass, more preferably 3.0 to 15.0 parts by mass, and even more preferably 6.0 to 10.0 parts by mass or less, relative to 100 parts by mass of the total amount of the cement clinker, the gypsum, and the admixture. By having the content of the hardening accelerator within the above-mentioned range, the hardening acceleration effect can be fully exerted, and the acceleration of setting and the decrease in fluidity can be suppressed.

[0064] The Blaine specific surface area of ​​the above-mentioned cement composition is preferably 3000 to 6000 cm 2 / g, and more preferably 3050 to 5000 cm 2 / g, and more preferably 3100 to 4500 cm 2 / g, and particularly preferably 3150 to 4000 cm 2 / g, and most preferably 3200 to 3800 cm 2 / g. The Blaine specific surface area is 3000 cm 2 / g or more, the strength development at the time of demolding is improved, and 2 When the molecular weight is 1.0 to 1.0 kg / g or less, the initial heat of hydration is reduced, and DEF can be further suppressed.

[0065] The above-mentioned cement composition can be produced, for example, by the following method. One embodiment of the method for producing a cement composition includes a step (mixing step) of mixing cement clinker having a C3S content of 20.0 to 80.0 mass% and a C3A content of 6.0 to 15.0 mass% calculated by the Bogue formula, gypsum, and an admixture.

[0066] In the above manufacturing method, in the above step, the blending of the cement clinker, the gypsum, and the admixture is adjusted so that the content of the gypsum is 1.8 to 3.5 mass% in terms of SO3, with the total amount of the cement clinker, the gypsum, and the admixture being 100 mass%, the content of the admixture is 2.0 to 30.0 mass%, with the total amount of the cement clinker, the gypsum, and the admixture being 100 mass%, and the C3S amount, the C3A amount, the coal ash content relative to 100 mass% of the total content of the cement clinker, the gypsum, and the admixture, and the amount of SO3 derived from the gypsum satisfy the relationship of the following formula (1). [C3S amount (mass%)]≦α×[C3A amount (mass%)-9.0]+2.0×[coal ash content (mass%)]+β-10.0×[SO3 amount (mass%)] …Formula (1)

[0067] The above α in the above formula (1) is a value represented by the following formula (2). α=(-2.5×[SO3 amount (mass%)])×(100-[gypsum hemihydrate ratio (mass%)]) / 100…Formula (2)

[0068] The proportion of gypsum hemihydrate in the above formula (2) indicates the proportion (mass%) of gypsum hemihydrate to the total amount of gypsum, and means the value calculated by the following formula (3). [Gypsum hemihydrate ratio (mass%)] = 100 × [total mass of gypsum hemihydrate (mass%)] / [total mass of gypsum (mass%)] ... Formula (3)

[0069] In the above formula (1), the above β is a real number of 75.0 or less, preferably 75.0, more preferably 70.0, and even more preferably 65.0. The lower the β, the more improved the DEF suppression effect.

[0070] The order of mixing the various components in the mixing step may be adjusted as appropriate. For example, the cement clinker and gypsum may be mixed first to prepare a base cement, and then the admixture may be mixed, or the cement clinker, gypsum, and admixture may be mixed at once. The mixing step may also serve as a grinding step for grinding the various components. For example, the above-mentioned production method may include a mixing step in which the cement clinker, gypsum, and admixture are put into a grinder and mixed and ground. By mixing the cement clinker, gypsum, and admixture in the mixing step, a cement composition having a superior DEF suppression effect can be produced.

[0071] The mixing of various components in the mixing step may be performed using a mixer such as a pan mixer, a tilting mixer, or a ribbon mixer. It is also possible to produce the cement composition by mixing and grinding the high C3A cement clinker, gypsum, and the above-mentioned coal ash in a grinding machine (such as a ball mill) during the grinding step of the cement clinker. This makes it possible to produce a cement composition with a high DEF suppression effect.

[0072] Although several embodiments have been described above, the present disclosure is not limited to the above-described embodiments. In addition, the descriptions of the above-described embodiments can be mutually applied. EXAMPLES

[0073] The present disclosure will be described in more detail below with reference to examples and comparative examples. However, the present disclosure is not limited to the following examples.

[0074] [Preparation of base cement (mixture of cement clinker and gypsum)] Table 1 shows the base cements (NC1 to NC6) used in the examples and comparative examples described below. The base cements (NC1 to NC6) were all made by adding gypsum dihydrate to cement clinker without adding any small amount of additives, and the Blaine specific surface area was 3300±100 cm 2 / g. The amount of gypsum dihydrate was adjusted and added so that the total amount of SO3 in the base cement was 1.9% by mass ± 0.1% by mass.

[0075] Table 1 shows the Blaine specific surface area of ​​the base cement, its chemical components, and the mineral composition of the cement clinker calculated by the Bogue formula. The Blaine specific surface area of ​​the base cement was calculated based on JIS R 5201 "Physical testing methods for cement." The chemical composition of the base cement and the mineral composition of the cement clinker were analyzed based on JIS R 5204 "Fluorescent X-ray analysis method for cement." The Simultix12 manufactured by Rigaku Corporation was used for the fluorescent X-ray analysis.

[0076] [Table 1]

[0077] [Coal ash (fly ash)] The coal ash (F1) used in the examples and comparative examples described later is shown in Table 2. Coal ash (FA1) was prepared by classifying coal ash collected from a thermal power plant using a swirling air separator (Turbo Classifier, manufactured by Nisshin Engineering Inc.) at 3000 rpm to remove coarse particles, and further classifying the resulting fine powder fraction at 6000 rpm to remove very fine particles and adjust the particle size before use.

[0078] The Blaine specific surface area and particle size of coal ash are shown in Table 2. The Blaine specific surface area of ​​coal ash was determined based on JIS R 5201 "Physical Testing Methods for Cement." The particle size distribution of coal ash was measured by dispersing the coal ash in ethanol using a laser diffraction particle size distribution analyzer SALD2200 manufactured by Shimadzu Corporation.

[0079] [Table 2]

[0080] [Limestone] The limestone (CC) used in the examples and comparative examples described below was a 325 mesh product (passed through a 45 μm sieve) manufactured by Ube Material Industries, Ltd. The 325 mesh product had a Blaine specific surface area of ​​7470 cm 2 / g, calcium carbonate content of 90 mass% or more, aluminum oxide content of 1.0 mass% or less, and conforming to the minor mixed components of JIS R 5210:2019 "Portland cement" were used. [Fine aggregate] In the DEF test and compressive strength measurement, standard sand for cement strength testing from the Cement Association (Inc.) was used as fine aggregate.

[0081] (Examples 1 to 12 and Comparative Example 4) The base cement, coal ash, and limestone were mixed and pulverized in the proportions (mass%) shown in Table 3 to prepare the cement composition. Gypsum dihydrate and hemihydrate were added in an external ratio so that the total amount of gypsum dihydrate and hemihydrate was 1.0 mass parts in terms of SO3 relative to 100 mass parts of the total amount of base cement (NC), coal ash (FA), and limestone (CC). The proportion of hemihydrate was calculated as the ratio of the total mass of hemihydrate to the total mass of gypsum in the cement composition. The amount of SO3 derived from gypsum in the cement composition was calculated as the amount of SO3 contained in gypsum in 100 mass% of the cement composition in mass%. Here, the molecular weight of gypsum dihydrate (2H2O·CaSO4) was 172, the molecular weight of hemihydrate (0.5H2O·CaSO4) was 145, and the molecular weight of SO3 was 80.

[0082] [Table 3]

[0083] [DEF test and compressive strength measurement] (Preparation of mortar composition) Each composition prepared in the Examples and Comparative Examples was mixed with standard sand for cement strength testing by the Japan Cement Association (Inc.) as fine aggregate, and water to prepare a mortar composition in accordance with the method described in JIS R 5201:2015 "Physical Testing Methods for Cement." The composition of the mortar composition is shown in Table 4.

[0084] [Table 4]

[0085] (DEF Test) The total SO3 content in the cement composition was adjusted to 6.2% by mass, and pre-cured at a high temperature of 90°C to create conditions conducive to the generation of DEF. This was because, in the absence of high-temperature curing and an increase in the amount of SO3, expansion due to DEF may not occur, and the above adjustments were made to facilitate observation.

[0086] More specifically, potassium sulfate was added to the mortar composition as a hardening accelerator, and the mixture was then kneaded and molded. The mold was then sealed and placed in a thermostatic chamber, cured at 20°C for 4 hours, heated to 90°C for 2 hours, and held at 90°C for 12 hours. After 12 hours, the temperature was lowered to 20°C for 4 hours, and cured at 20°C for 2 hours. The mixture was then demolded to obtain a hardened cement body (here, a hardened mortar body).

[0087] The hardened mortar bodies prepared by the above method were cured underwater in a thermostatic chamber at 20°C, and the length change of three hardened mortar bodies was measured for each level. The length change was measured using a dial gauge in accordance with the description of JIS A 1129-3:2010 "Method of measuring length change of mortar and concrete". The length change was measured by taking the hardened mortar bodies out of the water on the 7th, 14th, and 28th days after the age of underwater curing, and every 28 days thereafter, with the base length at the time of removal from the form as the time of removal. The length change was measured at four points on the front and back of two hardened mortar bodies, and the average value was taken as the length change of the target hardened mortar body. The value obtained by dividing the length change by the interval (100 mm) of the strain gauge was taken as the expansion coefficient of the hardened mortar body, and the degree of the expansion suppression of the hardened mortar body due to DEF was evaluated for the hardened mortar bodies on the 112th day of underwater curing according to the following criteria. If the evaluation was C or higher, it was judged that the effect of suppressing the expansion of the hardened mortar due to DEF was sufficient for practical use. The results are shown in Table 5. A: The expansion coefficient of the hardened mortar is 0.03% or less. B: The expansion coefficient of the hardened mortar is greater than 0.03% and less than 0.05%. C: The expansion coefficient of the hardened mortar is greater than 0.05% and less than 0.10%. D: The expansion rate of the hardened mortar exceeds 0.10%.

[0088] (Compressive strength measurement when demolded) The compressive strength was measured when demolded 24 hours after mixing. The compressive strength was measured in accordance with the method described in JIS R 5201:2015 "Physical Test Methods for Cement." Measurement was performed on one of the three pieces, and the average value obtained from two measurements was taken as the compressive strength when demolded, and was evaluated according to the following criteria. Each hardened mortar was evaluated according to the following criteria. A rating of D or higher was deemed to have excellent compressive strength. The results are shown in Table 5. A: Compressive strength is 40 MPa or more. B: Compressive strength is 37.5 MPa or more and less than 40 MPa. C: Compressive strength is 32 MPa or more and less than 37.5 MPa. D: Compressive strength is 30 MPa or more and less than 32 MPa. E: Compressive strength is 20 MPa or more and less than 30 MPa. F: Compressive strength is less than 20 MPa.

[0089] [Table 5]

[0090] As shown in Table 5, from the results of Examples 1-2 and Comparative Examples 1-4 in which the proportion of gypsum hemihydrate is 0% by mass, it was confirmed that the mortar compositions of Examples 1-2, which satisfy the relationship of formula (1), have a low expansion rate of the hardened mortar body due to DEF and sufficient compressive strength at the time of demolding, unlike the compositions of Comparative Examples 1-4 which do not satisfy the relationship of formula (1). In addition, when comparing the results of Examples 3-5 and Comparative Examples 5-7 in which the proportion of gypsum hemihydrate is about 40% by mass, it was confirmed that by satisfying the relationship of formula (1), the expansion of the hardened mortar body due to DEF is suppressed and the compressive strength at the time of demolding is also excellent.

[0091] From a comparison between the composition of Comparative Example 1 containing the same base cement (NC2) and the mortar composition of Example 4, it was confirmed that by increasing the proportion of hemihydrate gypsum from 0% by mass to around 40% by mass and adjusting the mix to satisfy the relationship of formula (1), the expansion of the hardened mortar body accompanying DEF can be suppressed and the compressive strength at the time of demolding can also be improved. It was confirmed that the expansion of the hardened mortar body accompanying DEF can be suppressed by increasing the proportion of hemihydrate gypsum. Similarly, from a comparison between Examples 1 and 3, and Examples 2 and 5 containing the same base cement, it was confirmed that the compressive strength at the time of demolding increases by increasing the proportion of hemihydrate gypsum from 0% by mass to around 40% by mass and adjusting the mix to satisfy the relationship of formula (1).

[0092] In addition, the composition of Reference Example 1 and the mortar composition of Example 2 have the same materials and the same mix, except for the amount of gypsum added. Reference Example 1 satisfies the requirements of the cement composition according to the present disclosure, except for the amount of SO3 relative to the total of cement clinker, gypsum, and admixtures, but the strength at the time of demolding is insufficient. On the other hand, when the mortar composition of Example 2, which satisfies the requirements of the cement composition of the present disclosure, including the amount of SO3 derived from gypsum by externally adding gypsum, was used, it was confirmed that the compressive strength at the time of demolding was greatly increased. [Industrial Applicability]

[0093] According to the present disclosure, it is possible to provide a cement composition that can produce a hardened cement body that has excellent compressive strength when demolded after high-temperature curing by suppressing expansion associated with DEF, even when the amounts of SO3 and C3A are high, while still allowing the production of a reduced amount of CO2 emissions during cement production compared to conventional methods, and a method for producing the same.

Claims

1. C calculated by the Bogue formula 3 The amount of S is 20.0 to 80.0 mass%, and C 3 Cement clinker having an A content of 6.0 to 15.0 mass%; Plaster and and The content of the gypsum is, when the total amount of the cement clinker, the gypsum and the admixture is 100 mass%, 3 This is calculated as 1.8 to 3.5 mass%. The content of the admixture is 2.0 to 30.0% by mass, with the total amount of the cement clinker, the gypsum, and the admixture being 100% by mass; The admixture includes coal ash, The content of the coal ash is 7.5% by mass or less, where the total content of the cement clinker, the gypsum, and the admixture is 100% by mass; Said C 3 The amount of S and the C 3 A amount of the cement clinker, the gypsum and the admixture, the coal ash content relative to 100 mass% of the total content of the cement clinker, the gypsum and the admixture, and the SO 2 derived from the gypsum. 3 The quantity and [C 3 S amount (mass %)] ≤ α × [C 3 A content (mass %) - 9.0] + 2.0 × [coal ash content (mass %)] + β - 10.0 × [SO 3 Amount (mass %)] …Formula (1) [In the formula (1), the α is α=(-2.5×[SO 3 [mass %]] × (100 - [hemihydrate gypsum content (mass %)]) / 100 ... Formula (2) The ratio of gypsum hemihydrate indicates the ratio of gypsum hemihydrate to the total amount of gypsum, and the ratio of gypsum hemihydrate is 0 to 90 mass%, The β is a real number of 75.0 or less. A cement composition which satisfies the relationship:

2. The cement clinker is SO 3 and R 2 Contains O, The SO 3 The amount is 0.10 to 2.00 mass %, and the R 2 The cement composition according to claim 1, wherein the O content is 0.10 to 2.00 mass%.

3. Blaine specific surface area is 3000 to 6000 cm 2 The cement composition according to claim 1 or 2, wherein the Cement content is 1 / g.

4. the admixture comprises limestone; The cement composition according to any one of claims 1 to 3, wherein the content of the limestone is 2.0 to 22.5 mass% based on the total amount of the admixture.

5. The admixture comprises coal ash, The cement composition according to any one of claims 1 to 4, wherein the coal ash content is 15.0 to 85.0 mass% based on the total amount of the admixture.

6. The Blaine specific surface area of ​​the coal ash is 3900 to 10000 cm 2 The cement composition according to any one of claims 1 to 5, wherein the Cementitious Agent is Cr, Mn, MnO ...

7. The cement composition according to any one of claims 1 to 6, wherein the coal ash has a 4 μm residue of 40 to 85 vol% and a 32 μm residue of 0 to 20.0 vol%.

8. Further containing a curing accelerator, The cement composition according to any one of claims 1 to 7, wherein the content of the hardening accelerator is 0.1 to 20.0 parts by mass relative to 100 parts by mass of a total amount of the cement clinker, the gypsum, and the admixture.

9. C calculated by the Bogue formula 3 The amount of S is 20.0 to 80.0 mass%, and C 3 The method includes a step of mixing cement clinker having an A content of 6.0 to 15.0 mass%, gypsum, and an admixture, The admixture includes coal ash, The content of the coal ash is 7.5% by mass or less, where the total content of the cement clinker, the gypsum, and the admixture is 100% by mass; In the above process, the content of the gypsum is determined based on the total amount of the cement clinker, the gypsum, and the admixture being 100 mass%. 3 The content of the admixture is 2.0 to 30.0 mass% when the total amount of the cement clinker, the gypsum, and the admixture is 100 mass%, and the C 3 The amount of S and the C 3 A amount of the cement clinker, the gypsum and the admixture, the coal ash content relative to 100 mass% of the total content of the cement clinker, the gypsum and the admixture, and the SO 2 derived from the gypsum. 3 The quantity and [C 3 S amount (mass %)] ≤ α × [C 3 A content (mass %) - 9.0] + 2.0 × [coal ash content (mass %)] + β - 10.0 × [SO 3 Amount (mass %)] …Formula (1) [In the formula (1), the α is α=(-2.5×[SO 3 [mass %]] × (100 - [hemihydrate gypsum content (mass %)]) / 100 ... Formula (2) The ratio of gypsum hemihydrate indicates the ratio of gypsum hemihydrate to the total amount of gypsum, and the ratio of gypsum hemihydrate is 0 to 90 mass%, The β is a real number of 75.0 or less. The method for producing a cement composition is characterized in that the proportions of the cement clinker, the gypsum, and the admixture are adjusted so as to satisfy the relationship.

Citation Information

Patent Citations

  • Sulfate and acid resistant concrete and mortar

    JP1998504511A

  • Cement composition and cement kneaded product

    JP2006001796A

  • Cement composition for steam cured product, mortar for steam cured product and concrete for steam cured product using the same

    JP2007176774A

  • Curing accelerator for cement and cement composition

    JP2014152063A

  • JP2016,2016,